Inovasi Sosial : Tipologi Ekonomi Politik Berbasis Etnis pada Masyarakat di Kelurahan Sungai Selan Bangka Tengah - Eka Mawar Hartati; Bustami Rahman; Ibrahim Ibrahim (Jurnal Studi Inovasi, 2023)
The background of this research is that the economy of the Sungai Selan community can be categorized as quite good and has progressed from previous years. In this case, the economic progress of the Sungai Selan community itself is supported by various types of livelihoods and the abundance of natural resource potential. The first source of livelihood for the people of Sungai Selan, who incidentally are farmers and fishermen, they also work as traders, as carpenters, and many other jobs. The aims of this research are: (1) to find out the typology of ethnic-based political economy; (2) to find out what factors money causes the formation of the political economy typology. This research uses qualitative methods because it is done naturally. Where the qualitative method is carried out based on data collection techniques, inductive data analysis and is carried out through data collection with participant observation to find out this phenomenon. This study was analyzed using the Need For Achievement theory (need for achievement) put forward by David McClelland and a rational choice put forward by James Coleman. and nature, interest factors, and origin factors. There are several policy innovations that the researcher presents.